Developing a Digital Tourism Village Community Empowerment Typology: Evidence from the Godevi Marketplace in Sayan Village Bali - Sanjiwani, Ni Made Gandhi (Lembaga Pengembangan Kinerja Dosen, 2026)
Tourism villages have become a strategic approach to promoting sustainable rural development in Indonesia. However, many villages continue to face limited digital capabilities, restricted market access, and inadequate community empowerment despite the growing adoption of digital technologies. Existing studies mainly emphasize the promotional and economic functions of digital platforms while overlooking their contribution to multidimensional community empowerment. This study investigates how the Godevi digital marketplace, through its Sustainability, Empowerment, and Entrepreneurship (SEE) framework, enhances community empowerment in Sayan Tourism Village, Bali, and develops a Digital Tourism Village Community Empowerment Typology. A descriptive qualitative case study was conducted using in-depth interviews, field observations, focus group discussions, and document analysis involving representatives of the Tourism Awareness Group (Pokdarwis), village government, village-owned enterprises, tourism operators, and Godevi management. The findings indicate that Godevi serves not only as a digital marketplace but also as a sociopreneurial platform that strengthens economic, social, psychological, and political empowerment. The SEE framework supports sustainable tourism product development, improves community capacity through participatory governance, enhances digital entrepreneurship, reinforces cultural identity and social cohesion, and increases local involvement in tourism decision-making. Based on these findings, this study proposes a Digital Tourism Village Community Empowerment Typology that integrates the SEE framework with multidimensional community empowerment. This typology advances digital tourism scholarship by providing a systematic framework for explaining how digital platforms facilitate community-centred tourism development and offers practical guidance for policymakers, tourism village managers, and sociopreneurs in implementing inclusive and sustainable digital transformation.